Frozen: Children in Argumentation Between the Agonistic and Cooperation - Hannken-Illjes, Kati; Bose, Ines (Informal Logic)

(untitled) (Informal Logic, 2019)
In this study, we consider the ways different degrees of dissent are established in interaction, especially in interactions among children. One important aspect in the development of the ability to argue is the framing of interactions as rather cooperative or agonistic. Different framings seem to allow for different forms of argumentative activity. The focus in this paper is on the mediation of degrees of dissensus in argumentation in child-child communication. It is established, we argue, through verbal as well as non-verbal means, and the agonistic and cooperativity can be indicators for the space argumentation has in child-child interaction.